New insights into the potential cardioprotective effects of telmisartan and nanoformulated extract of Spirulina platensis via regulation of oxidative stress, apoptosis, and autophagy in an experimental model - May Almukainzi; Thanaa A. El-Masry; Hanaa A. Ibrahim; Hebatallah M. Saad; Enas I. El Zahaby; Asmaa Saleh; Maysa M. F. El-Nagar (Frontiers Media S.A., 2024)
BackgroundCardiotoxicity is one of the limiting side effects of the commonly used anticancer agent cyclophosphamide (Cyclo).Materials and methodsThe possible protective effects of telmisartan and nanoformulated Spirulina platensis (Sp) methanolic extract against Cyclo-induced cardiotoxicity were examined in this study. Experimental groups of rats were randomly divided into nine groups as control vehicle, control polymer, telmisartan (TEL, 10 mg/kg), free Sp extract (300 mg/kg), nano Sp extract (100 mg/kg), Cyclo (200 mg/kg), TEL + Cyclo, free Sp + Cyclo, and nano Sp + Cyclo. The groups with Cyclo combinations were treated in the same manner as their corresponding ones without Cyclo, with a single dose of Cyclo on day 18.ResultsThe results indicate that Cyclo causes significant cardiotoxicity, manifesting in the form of notable increases of 155.49%, 105.74%, 451.76%, and 826.07% in the serum levels of glutamic oxaloacetic transaminase (SGOT), lactate dehydrogenase (LDH), creatine kinase MB (CK-MB), and cardiac troponin I (cTnI) enzyme activities, respectively, as compared to the control. In addition, the cardiac glutathione (GSH) content and activity of glutathione peroxidase-1 (GPX-1) enzyme decreased by 65.94% and 73.85%, respectively. Treatment with nano Sp extract showed the most prominent restorations of the altered biochemical, histopathological, and immunohistochemical features as compared with those by TEL and free Sp; moreover, reductions of 30.64% and 43.02% in the p-AKT content as well as 60.43% and 75.30% of the endothelial nitric oxide synthase (eNOS) immunoreactivity were detected in the TEL and free Sp treatment groups, respectively. Interestingly, nano Sp boosted the autophagy signal via activation of beclin-1 (36.42% and 153.4%), activation of LC3II (69.13% and 195%), downregulation of p62 expressions (39.68% and 62.45%), and increased gene expressions of paraoxonase-1 (PON-1) (90.3% and 225.9%) compared to the TEL and free Sp treatment groups, respectively.ConclusionThe findings suggest the protective efficiency of telmisartan and nano Sp extract against cardiotoxicity via activations of the antioxidant, antiapoptotic, and autophagy signaling pathways.